Aid absorption and spending in Africa: A panel cointegration approach - Pedro M. G. Martins (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2010)
This paper focuses on the macroeconomic management of large inflows of foreign aid. It investigates the extent to which African countries have coordinated fiscal and macroeconomic responses to aid surges. In practice, we construct a panel dataset to investigate the level of aid 'absorption' and 'spending'. This paper departs from the recent empirical literature by utilising better measures for aid inflows and by employing cointegration analysis. The empirical short-run results suggest that, on average, Africa's low-income countries have absorbed two-thirds of (grant) aid receipts. This suggests that most of the foreign exchange provided by the aid inflows has been used to finance imports. The other third has been used to build up international reserves, perhaps to protect economies from future external shocks. In the long-run, absorption increases but remains below its maximum ('full absorption'). Moreover, we also show that aid resources have been fully spent, especially in support of public investment. There is only weak evidence that a share of aid flows have been 'saved', i.e. substituted domestic borrowing. Overall, these findings suggest that the macroeconomic management of aid inflows in Africa has been significantly better than often portrayed in comparable exercises. The implication is that African countries will be able to efficiently manage a gradual scaling up in aid resources.
Keywords: C23; F35; O23; O55; 330; Macroeconomic Management; Foreign Aid; Panel Data; Africa; Entwicklungshilfe; Kapitalimport; Entwicklungspolitik; Afrika